Long-Term Antipsychotic Effectiveness and Comparison of the Efficacy of Monotherapy and Polypharmacy in Schizophrenia: A 3-Years Follow-Up “Real World” Study in China - Zhang, Lei; He, Sidi; He, Luyao; Yu, Wenjuan; He, Shen; Li, Yange; Yu, Yimin; Zheng, Qingshan; Huang, Jingjing; Shen, Yifeng; Li, Huafang (Frontiers in Pharmacology, 2022)
Background: Discontinuation of antipsychotic treatment is a common problem in patients with schizophrenia and could reduce the effectiveness of treatment. Time to discontinuation (TTD) is one of the indicators of compliance and may also be an effective indicator of medication efficacy. The aim of the study was to compare the clinical effectiveness of quetiapine, olanzapine, risperidone, and aripiprazole in the real-world treatment of schizophrenia with 3-year follow-up. Method: A multi-center, open, cohort, prospective, real-world study was conducted. 706 patients were analyzed without intervention in medication selection and use, followed up for 3 years. Kaplan-Meier survival curves were used to draw the treatment discontinuation rates (TDR) curves at each time point. Cox proportional hazard regression model was used to assess the relative risk of TTD of antipsychotics. Results: There was a significant difference among monotherapy groups in all-cause antipsychotic treatment discontinuation (p=0.0057). Among the four medications, the TDR of risperidone was the highest. Compared with polypharmacy, except for aripiprazole, the TDR of other three monotherapy medications were lower than that of polypharmacy, and olanzapine was statistically different (p=0.0325). The cox regression analysis showed that after correction of Hochberg with multiple tests, only olanzapine had a relative risk lower than risperidone (p < 0.0083). Conclusions: The findings indicated that risperidone monotherapy had the highest TDR and the shortest TTD. Olanzapine was superior to the other three antipsychotics and olanzapine monotherapy was superior to polypharmacy